(3GdETGQI aj COdI GdTQYs - (3SdjeGf Hf Nda Hf SYO GdJLjHj GdbQWHj, CHh GdhdjO GdHGLj,J (B474 (3g` s
(3ChdgG (B:s
(3jHOC HHGH GbSGe COdI GdTQY (B( (3COdI GdTY Ydi KdGKI CVQH CUd heYbhd CUd hESJUMGH MGd (B) s
(3BNQgG (B:s
(3dCf cd Ua jMJGL ai EKHGJg Edi VQH ef GdELJgGO hcd eG ESJZfi GdOdjd Yf cKQI GdELJgGO ced cJGH GdETGQI ddHGLi hGdMeO ddg Ydi MSf Yhfg hUdhGJg Ydi eMeO hYdi Bdg hSde JSdjekG s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH (B3s
(3GdfSNI HgG MhGTs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B3 - (3U (B125 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B4 - (3U (B261s
(3JHUQGJ GdCUd (B:s
(3MGdI GdfSNI LjOI s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3CUhd Gdabgs